Rural crime control – thematic analysis on discussions and perceptions of rural crime control in Finland - Nieminen, Sanni (My University, 2021)
The study observes discussions and understanding of rural crime control in chosen public documents of the Finnish Ministry of the Interior and the National Police Board of Finland. The aim of the analysis is to observe how rural crime control is understood and discussed in the selected public documents. The method of the study is thematic analysis. Documents have been coded, and themes have been formed with latent approach. Discussions of rural crime control in the documents are observed from three different perspectives: how crime control is measured and evaluated in the documents, what kind of challenges are identified for rural crime control and how “rural” is discussed in the context of rural crime control. By looking into measures, challenges and context of rural crime control, I hope to gain information on overall discussions of rural crime control. The results indicate that there were three main themes which were present in the discussion of rural crime control: spatial and temporal control, the effectiveness of control and the equality of control. In addition to these themes, there were some notions which could be described as urban control: texts produced some understandings of urban as “normal” space.

Tämä tutkielma on maaseutukriminologian alaan kuuluva tutkimus maaseutualueiden rikoskontrollista. Tutkielma pyrkii tarkastelemaan miten maaseutualueiden rikoskontrollista puhutaan ja miten maaseutualueiden rikoskontrolli käsitetään valituissa Sisäministeriön ja Poliisihallituksen raporteissa. Tutkielma keskittyy tutkimaan niitä tapoja, joilla maaseutualueiden rikoskontrolli kuvataan ja ymmärretään valituissa raporteissa. Tutkimus on toteutettu teema-analyysina. Maaseutualueiden rikoskontrollin kuvauksia ja keskustelua on tutkittu tutkimuksessa erityisesti kolmesta eri näkökulmasta: miten rikoskontrollia mitattiin ja arvioitiin raporteissa, millaisia uhkia raporteissa nähtiin maaseudun rikoskontrollille ja miten maaseudusta keskusteltiin rikoskontrollin yhteydessä. Tarkastelemalla raporteissa esitettyjä ajatuksia kontrollin mittareista, haasteista ja kontekstista, pyrin saamaan tietoa niistä teemoista, joilla maaseutualueiden rikoskontrollista on yleisesti raporteissa puhuttu. Tutkimuksen tulokset osoittavat, että raporteista oli löydettävissä kolme pääteemaa, jotka esiintyivät teksteissä maaseutualueiden rikoskontrollista puhuttaessa: tilallis-ajallinen kontrolli, tehokas kontrolli ja yhdenvertainen kontrolli. Näiden lisäksi raporteissa oli nähtävissä teema, jota voisi kuvailla ”taajamalähtöiseksi kontrolliksi”. Käytännössä tämä tarkoittaa, että raporteissa oli osittain nähtävissä ajatus kaupungista ”normaalina” ympäristönä.
Keywords: rural criminology, crime control, spatial control, thematic analysis